A type II endoleak from an accessory renal artery treated with laser assisted, transgraft coil embolization: A case report - Marco Panagrosso, MD; Katarina Björse, MD; Timothy Resch, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
The main complications of coverage accessory renal artery (ARA) are renal infarction and potentially renal function impairment and type II endoleak if firm apposition to the aortic wall is not achieved. We describe the management of an ARA type II endoleak treated by laser-assisted, transgraft coil embolization (LATE). A 76-year-old patient underwent a computed tomography scan 4 years after endovascular aneurysm repair. The computed tomography scan showed an increase of sac diameter with type II endoleak originating from the left ARA as an effect of aortic neck dilatation. ARA embolization was performed successfully via fusion-guided laser in situ fenestration and standard coil placement.